Empat Plus Satu untuk Swing Trader - Ronny Thomas; Nurlia Nurlia (Jurnal Pasar Modal dan Bisnis, 2021)
This research focuses on technical analysis, which gives signals to trading stocks when to enter, and when to exit the market, in a transaction in the capital market. The indicators used are RSI, MACD histogram, stochastic, ADX, and + candlesticks. During the Covid 19 pandemic, where prices were moving SIDEWAYS. The concept of "Four Plus One for Swing Traders" has been quite successful with the application of shares in the LQ45 and IDXSMC-LIQ Index. The purpose of this study was to determine the technical indicators of analysis correctly and profitably. This research method uses qualitative analysis techniques by screening stocks with four criteria plus one technical analysis in the form of candlesticks. The results of this study indicate a tendency to generate a significant return on the Indonesian stock market. Stocks that generate positive returns (profit) such as shares of Astra International, Tbk, Bank BTN Tbk, Bank Mandiri Tbk, Excel Asia Tbk, Bank Bukopin Tbk, Indika Tbk, United Tractor Tbk. Meanwhile, shares that suffered losses were Unilever Tbk shares. The implication of this research is that the technical analysis of four plus one for swing traders can be used by investors and potential investors to make decisions whether to buy or sell portfolios.